Lateralised Behavioural Responses of Chickens to a Threatening Human and a Novel Environment Indicate Fearful Emotions - Amira A. Goma; Clive J. C. Phillips (Animals, 2025)
The demeanour of a human during an interaction with an animal may influence the animal’s emotional response. We investigated whether the emotional responses of laying hens to a threatening or neutral human and a novel environment were lateralised, from which their emotional state can be inferred. Twenty-five DeKalb white laying hens reared in furnished cages under environmentally controlled conditions were individually assessed for their responses to these stimuli. They were contained in a box before emerging into an arena with a threatening human, who attempted direct eye contact with the bird and had their hands raised towards it, or a neutral person, who had no eye contact and sat with their hands on their knees. When initially placed in the box adjacent to the test arena, birds that remained in the box used their left eye more than their right eye, and they showed evidence of nervousness, with many head changes, neck stretching, and vocalisation. Birds showed lateralised behaviour in both the box and arena. Birds entering the arena with the threatening person used their left eye (connected to the right brain hemisphere) more than their right eye, usually with their body less vertical, and were more likely to be standing than sitting, compared with those viewing the neutral person. This confirms the bird’s interpretation of the person as threatening, with left eye/right brain hemisphere processing of flight or fight situations. We conclude that lateralised responses of chickens suggest that a threatening person is viewed more fearfully than a neutral person. However, further investigation is required with a larger sample of birds to strengthen these findings and enhance the generalisability of behavioural responses.